Coping Mechanism of Persons Deprived of Liberty in Caloocan City Jail: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study was conducted to determine, analyze, and assess the coping mechanismof persons deprived of liberty inside Caloocan City Jail with the participation of the detaineesand jail officers. The jails or prison facilities were a stressful environment for the citizens orother civilians being locked up inside. This could lead to getting involved in a gang, involving incommitting different crimes, involvement to transferring illegal contraband, and the negativeimpact on mental or physical health that cause of being a recidivist of detainees or else the riskof getting involved in suicidal thoughts to relieve the stress and other mental negative effectsof being locked up inside of jails. However, there are methods, techniques, or strategies onhow to get rid of this kind of stress for the detainees or prisoners inside facilities. The so-calledcoping mechanism of persons deprived of liberty is to prevent negative behavior and preventrisk safety concerns of detainees.The results showed that regular exercises, religious gatherings, and engaging in any otheractivities were interpreted as strongly agreeing. Moreover, the problems encountered, whichwere congestion of jails, quality and quantity of food, and violent crimes, were interpreted asstrongly agreeing. There were proposed measures that may be utilized to address the safetyconcerns of persons deprived of liberty. The study was finalized by the researcher uponassessment of data gathering from the two (2) groups of respondents to determine theeffective coping mechanism of PDL.The researcher conducted the study upon the first assessment, the regular exercises of thepersons deprived of liberty, which it turned out that it was effectively implemented, well-established, and effective for the coping mechanism, including developing physical andmental health; it can reform the behavior, and it spends more time outside of jails rather thanbeing locked up.
Keywords: Social Sciences